Foam sheet and synthetic leather

By controlling the content of the urethane resin and the absence of organic solvents in the urethane resin aqueous dispersion, combined with mechanical foaming and gas introduction technology, the problem that the urethane resin aqueous dispersion cannot form an intermediate porous layer in the prior art is solved, and a foamed sheet with excellent foam retention, feel and peel strength is achieved.

CN114364745BActive Publication Date: 2025-03-28DIC CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202080060638.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-10-28
Filing Date
2020-09-17
Publication Date
2025-03-28
Estimated Expiration
2040-09-17

AI Technical Summary

Technical Problem

The existing urethane resin aqueous dispersion cannot form an intermediate porous layer, resulting in poor problems such as hand feel and bending resistance, and it is difficult to control the size and amount of bubbles.

Method used

The aqueous dispersion of urethane resin is used, and the content of urethane resin is 50 to 80 mass%, and does not contain organic solvents. The foamed sheet is formed by mechanical foaming and gas introduction technology.

Benefits of technology

The foam sheet with excellent foam retention, feel and peel strength is achieved, and is suitable as the intermediate layer of synthetic leather.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003520896710000191
    Figure BDA0003520896710000191
  • Figure BDA0003520896710000211
    Figure BDA0003520896710000211
  • Figure BDA0003520896710000212
    Figure BDA0003520896710000212
Patent Text Reader

Abstract

The problem to be solved by the present invention is to provide a foam sheet with excellent bubble retention, hand feel and peel strength. The present invention provides a foam sheet, characterized in that it is a foam sheet formed by an aqueous dispersion of a urethane resin (X), the content of the urethane resin (X) in the aqueous dispersion is 50 to 80% by mass, and the aqueous dispersion does not contain an organic solvent. In addition, the present invention provides a synthetic leather, characterized in that it has at least a substrate (i) and a polyurethane layer (ii), and the polyurethane layer (ii) is formed by the foam sheet. The density of the foam sheet is preferably 200 to 1000 kg / m 3 .
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a foam sheet and synthetic leather. Background Art

[0002] Urethane resins are widely used in the manufacture of synthetic leather (including artificial leather), coating agents, adhesives, gloves, clothing, etc. due to their good mechanical strength and hand feel. For the above-mentioned urethane resins, solvent-based urethane resins containing N,N-dimethylformamide (DMF) have been the mainstream so far. However, in the context of DMF regulation in Europe, strengthening of VOC emission regulation in China, and DMF regulation by large clothing manufacturers, environmental coordination measures such as weak solvent, water-based, and solvent-free are required.

[0003] Under such circumstances, a carbamate resin aqueous dispersion (polyurethane dispersion) obtained by dispersing a carbamate resin in water has begun to be used for the above-mentioned purposes. However, the above-mentioned carbamate resin aqueous dispersion cannot obtain an intermediate porous layer formed by wet coagulation of a conventional solvent-based carbamate resin, and therefore has problems such as poor hand feel and bending resistance. As a method for solving this problem, a method of mixing microcapsules in a carbamate resin aqueous dispersion and a mechanical foaming method for dispersing gas have been proposed (for example, refer to Patent Document 1). However, in the former method, the hardening of the hand feel or the poor smoothness caused by the expansion of the microcapsules become problems. In addition, in the latter method, when the carbamate resin aqueous dispersion is dried, the bubbles in the mixed liquid merge into one and disappear, so it is extremely difficult to control the size and amount of the bubbles.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2013-119688 Summary of the invention

[0007] Problems to be solved by the invention

[0008] An object of the present invention is to provide a foam sheet having excellent foam retention, texture and peel strength.

[0009] Means for solving problems

[0010] The present invention provides a foam sheet, characterized in that it is formed from a water dispersion of a urethane resin (X), the content of the urethane resin (X) in the water dispersion is 50 to 80% by mass, and the water dispersion does not contain an organic solvent.

[0011] The present invention also provides a synthetic leather characterized by comprising at least a substrate (i) and a polyurethane layer (ii), wherein the polyurethane layer (ii) is formed of the foam sheet.

[0012] Effects of the Invention

[0013] The foam sheet of the present invention is excellent in foam retention, hand feel and peel strength. Therefore, the foam sheet of the present invention can be particularly suitably used as an intermediate layer of synthetic leather. DETAILED DESCRIPTION

[0014] The foam sheet of the present invention is formed from a specific urethane resin (X) aqueous dispersion.

[0015] The urethane resin aqueous dispersion contains 50 to 80% by mass of the urethane resin (X) and contains no organic solvent.

[0016] In the present invention, the content of the above-mentioned carbamate resin (X) must be in the range of 50 to 80% by mass. In this way, by making the so-called carbamate resin (X) in the water dispersion have a high solid content, even if bubbles are added by mechanical foaming or gas introduction, the bubble retention is excellent, and the dryness of the carbamate resin water dispersion is improved, so that the foamed sheet will not produce cracks during and / or after drying, and excellent hand feel, plane smoothness and peel strength can be obtained. In addition, since the solid content of the carbamate resin (X) is high, the line speed when the water is dried can also be increased. As the content of the above-mentioned carbamate resin (X), from the perspective of obtaining a more excellent hand feel, plane smoothness and peel strength, it is preferably in the range of 53 to 70% by mass, more preferably in the range of 55 to 70% by mass, and further preferably in the range of 57 to 65% by mass.

[0017] The above-mentioned carbamate resin (X) can be dispersed in water, for example, a carbamate resin having a hydrophilic group such as anionic group, cationic group, nonionic group, etc.; a carbamate resin forcibly dispersed in water with an emulsifier, etc. can be used. These carbamate resins can be used alone or in combination of two or more. Among them, from the aspects of manufacturing stability and water dispersion stability, it is preferred to use a carbamate resin having a hydrophilic group, and more preferably a carbamate resin having anionic group and / or nonionic group.

[0018] Examples of a method for obtaining the urethane resin having an anionic group include a method using, as a raw material, one or more compounds selected from a diol compound having a carboxyl group and a compound having a sulfonyl group.

[0019] Examples of the diol compound having a carboxyl group include 2,2-dimethylolpropionic acid, 2,2-dimethylolbutyric acid, 2,2-dimethylolbutyric acid, 2,2-dimethylolpropionic acid, and 2,2-pentanoic acid. These compounds may be used alone or in combination of two or more.

[0020] As the above-mentioned compound having a sulfonyl group, for example, 3,4-diaminobutanesulfonic acid, 3,6-diamino-2-toluenesulfonic acid, 2,6-diaminobenzenesulfonic acid, N-(2-aminoethyl)-2-aminosulfonic acid, N-(2-aminoethyl)-2-aminoethylsulfonic acid, N-2-aminoethane-2-aminosulfonic acid, N-(2-aminoethyl)-β-alanine, and salts thereof can be used. These compounds can be used alone or in combination of two or more.

[0021] As a method for obtaining the urethane resin having a nonionic group, for example, there is a method of using a compound having an oxyethylene structure as a raw material.

[0022] As the compound having an oxyethylene structure, for example, polyether polyols having an oxyethylene structure such as polyethylene glycol, polyoxyethylene polyoxypropylene glycol, polyoxyethylene polyoxytetramethylene glycol, and polyethylene glycol dimethyl ether can be used. These compounds can be used alone or in combination of two or more. Among them, polyethylene glycol and / or polyethylene glycol dimethyl ether are preferably used from the aspect of being able to more easily control hydrophilicity.

[0023] The number average molecular weight of the raw material used to obtain the urethane resin having a nonionic group is preferably in the range of 200 to 10,000, more preferably in the range of 300 to 3,000, and even more preferably in the range of 300 to 2,000, from the viewpoint of obtaining more excellent emulsification and water dispersion stability. The number average molecular weight of the raw material used to obtain the urethane resin having a nonionic group is a value measured by gel permeation chromatography (GPC).

[0024] Examples of a method for obtaining the urethane resin having a cationic group include a method of using one or two or more compounds having an amino group as a raw material.

[0025] As the compound having an amino group, for example, a compound having a primary amino group and a secondary amino group such as triethylenetetramine and diethylenetriamine; a compound having a tertiary amino group such as N-alkyldialkanolamines such as N-methyldiethanolamine and N-ethyldiethanolamine, N-methyldiaminoethylamine, and N-alkyldiaminoalkylamines such as N-ethyldiaminoethylamine, etc. These compounds may be used alone or in combination of two or more.

[0026] As the emulsifier that can be used when obtaining the above-mentioned urethane resin that is compulsorily dispersed in water, for example, nonionic emulsifiers such as polyoxyethylene nonylphenyl ether, polyoxyethylene lauryl ether, polyoxyethylene styrenylphenyl ether, polyoxyethylene sorbitol tetraoleate, polyethylene-polypropylene copolymer, etc. can be used; fatty acid salts such as sodium oleate, alkyl sulfate salts, alkylbenzene sulfonate salts, alkyl sulfosuccinate salts, naphthalene sulfonate salts, polyoxyethylene alkyl sulfate salts, sodium alkane sulfonate salts (アルカンスルフォネートナトリウム塩), sodium salts of alkyl diphenyl ether sulfonate, etc. can be used; cationic emulsifiers such as alkylamine salts, alkyltrimethylammonium salts, alkyl dimethylbenzylammonium salts, etc. can be used. These emulsifiers can be used alone or in combination of two or more.

[0027] As the above-mentioned urethane resin (X), specifically, for example, the reaction product of a chain extender (a1), a polyol (a2), a polyisocyanate (a3), and a compound (a4) having a hydrophilic group used as needed (the raw materials used to obtain the above-mentioned urethane resin having an anionic group, a urethane resin having a cationic group, and a urethane resin having a nonionic group) can be used.

[0028] As the above-mentioned chain extender (a1), a chain extender with a molecular weight less than 500 (preferably in the range of 50 to 450) can be used. Specifically, chain extenders having hydroxyl groups such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, hexamethylene glycol, sucrose, methylene glycol, glycerol, sorbitol, bisphenol A, 4,4'-dihydroxybiphenyl, 4,4'-dihydroxydiphenyl ether, trimethylolpropane, etc. can be used; chain extenders having amino groups such as ethylenediamine, 1,2-propanediamine, 1,6-hexamethylenediamine, piperazine, 2,5-dimethylpiperazine, isophoronediamine, 1,2-cyclohexanediamine, 1,3-cyclohexanediamine, 1,4-cyclohexanediamine, 4,4'-dicyclohexylmethanediamine, 3,3'-dimethyl-4,4'-dicyclohexylmethanediamine, 1,4-cyclohexanediamine, hydrazine, etc. can be used. These chain extenders can be used alone or in combination of two or more. It should be noted that the molecular weight of the above-mentioned chain extender (a1) represents the value calculated according to the chemical formula.

[0029] As the chain extender (a1), a chain extender having an amino group (hereinafter referred to as "amine chain extender") is preferably used from the viewpoint that the chain can be easily extended even at a relatively low temperature of 30° C. or less, the energy consumption during the reaction can be suppressed, and that the introduction of a urea group can provide more excellent mechanical strength, film-forming property, hand feel, and peel strength. Even when the solid content of the urethane resin (X) is increased, more preferably an amine chain extender having a molecular weight in the range of 30 to 250 is used from the viewpoint that more excellent foam retention, emulsification, and water dispersion stability can be obtained. In addition, when two or more chain extenders are used in combination, the molecular weight is an average value thereof, and the average value may be within the above-mentioned preferred molecular weight range.

[0030] The usage ratio of the chain extender (a1) is more preferably in the range of 0.1 to 30% by mass, particularly preferably in the range of 0.5 to 10% by mass, based on the total mass of the raw materials constituting the urethane resin (X), from the viewpoint of obtaining more excellent mechanical strength, film-forming property, hand feel, peel strength, foam retention, emulsification property, and water dispersion stability, and from the viewpoint of making it easier to increase the solid content of the urethane resin (X).

[0031] As the above-mentioned polyol (a2), for example, polyether polyol, polyester polyol, polyacrylic polyol, polycarbonate polyol, polybutadiene polyol, etc. can be used. These polyols can be used alone or in combination of two or more. It should be noted that, when the above-mentioned carbamate resin having a nonionic group is used as the above-mentioned carbamate resin (X), as the above-mentioned polyol (a2), a substance other than the raw material used to obtain the above-mentioned carbamate resin having a nonionic group is used.

[0032] The number average molecular weight of the polyol (a2) is preferably in the range of 500 to 100000, and more preferably in the range of 800 to 10000, from the viewpoint of the mechanical strength of the obtained film. The number average molecular weight of the polyol (a2) is a value measured by gel permeation chromatography (GPC).

[0033] The proportion of the polyol (a2) to be used is more preferably in the range of 40 to 90% by mass, particularly preferably in the range of 50 to 80% by mass, based on the total mass of the raw materials constituting the urethane resin (X) from the viewpoint of obtaining more excellent mechanical strength.

[0034] As the polyisocyanate (a3), for example, aromatic polyisocyanates such as phenylene diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, xylylene diisocyanate, naphthalene diisocyanate, polymethylene polyphenyl polyisocyanate, and carbodiimidized diphenylmethane polyisocyanate; aliphatic polyisocyanates or alicyclic polyisocyanates such as hexamethylene diisocyanate, lysine diisocyanate, cyclohexane diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, xylylene diisocyanate, tetramethylxylylene diisocyanate, dimer acid diisocyanate, and norbornene diisocyanate can be used. These polyisocyanates can be used alone or in combination of two or more.

[0035] The usage ratio of the polyisocyanate (a3) ​​is more preferably in the range of 5 to 40% by mass, particularly preferably in the range of 10 to 35% by mass, based on the total mass of the raw materials constituting the urethane resin (X) from the viewpoint of obtaining more excellent mechanical strength.

[0036] The proportion of the compound (a4) having a hydrophilic group to be used is preferably 5% by mass or less, more preferably 2% by mass or less, further preferably in the range of 0.25 to 2% by mass, and particularly preferably in the range of 0.5 to 1.8% by mass, based on the total mass of the raw materials constituting the urethane resin (X), from the viewpoint of obtaining more excellent foam retention, emulsification, water dispersion stability and film-forming properties.

[0037] The average particle size of the urethane resin (X) is preferably in the range of 0.01 to 1 μm, and more preferably in the range of 0.05 to 0.9 μm, from the viewpoint of obtaining more excellent foam retention, surface smoothness, hand feel, and film-forming properties. It should be noted that the method for measuring the average particle size of the urethane resin (X) is described in the Examples described below.

[0038] As water used in the present invention, ion exchange water, distilled water, etc. can be used. These waters may be used alone or in combination of two or more.

[0039] The urethane resin aqueous dispersion used in the present invention contains the above-mentioned urethane resin (X) and water as essential components, but may contain other additives as necessary.

[0040] As the above-mentioned other additives, for example, emulsifiers, crosslinking agents, neutralizers, thickeners, urethanization catalysts, fillers, pigments, dyes, flame retardants, leveling agents, anti-blocking agents, film-forming aids, foaming agents, etc. can be used. These additives can be used alone or in combination of two or more. These additives are appropriately determined according to the purpose of using the foam sheet. It should be noted that the urethane resin aqueous dispersion used in the present invention does not contain an organic solvent in its manufacturing process, but as the above-mentioned additive, it is allowed to contain an organic solvent.

[0041] Next, the method for producing the urethane resin aqueous dispersion used in the present invention will be described.

[0042] The method for producing the urethane resin aqueous dispersion used in the present invention comprises the steps of: reacting the polyol (a2), the polyisocyanate (a3) ​​and the compound (a4) having a hydrophilic group in the absence of a solvent to obtain a urethane prepolymer (i) having an isocyanate group (hereinafter referred to as the "prepolymer step"); then dispersing the urethane prepolymer (i) in the water (hereinafter referred to as the "emulsification step"); and then reacting the chain extender (a1) to obtain a urethane resin (X) (hereinafter referred to as the "chain extension step").

[0043] It is important that the prepolymer process is carried out in the absence of a solvent. In the prior art, the prepolymer process is usually carried out in an organic solvent such as methyl ethyl ketone or acetone, but a desolventizing process is required to distill off the organic solvent after the emulsification process, which requires several production days at the actual production site. In addition, it is also difficult to completely distill off the organic solvent in the desolventizing process, and some organic solvent often remains, making it difficult to completely respond to environmental protection measures. On the other hand, in the manufacturing method of the present invention, by carrying out the prepolymer process in the absence of a solvent, a urethane resin aqueous dispersion that does not contain any organic solvent can be obtained, and its production process can also be labor-saving.

[0044] In addition, when the prepolymer step is performed by the conventional method using an organic solvent, the urethane resin may not be emulsified, or even if it can be emulsified, the particle size of the obtained urethane resin may become large, and the region where a good urethane resin aqueous dispersion can be obtained is very limited. The reason for this has not been explained in detail, but it is believed that during emulsification, the ability of the hydrophilic group of the urethane resin is inhibited by the organic solvent, the neutralizing agent (for adjusting the acid value of the urethane resin having anionic groups), etc.

[0045] In contrast, in the present invention, by carrying out the prepolymer step in the absence of a solvent, it is possible to stably obtain an aqueous dispersion of a urethane resin having a small amount of introduced hydrophilic groups and having an average particle size equivalent to that of the conventional method obtained by reacting a chain extender, which is a region particularly difficult to obtain in the conventional method.

[0046] The molar ratio of the total of the hydroxyl groups of the polyol (a2) and the hydroxyl groups and amino groups of the compound (a4) having a hydrophilic group to the isocyanate groups of the polyisocyanate (a3) ​​in the prepolymer step [isocyanate groups / (hydroxyl groups and amino groups)] is preferably in the range of 1.1 to 3, and more preferably in the range of 1.2 to 2, from the viewpoint of obtaining more excellent foam retention, surface smoothness, film-forming properties, hand feel, peel strength and mechanical strength.

[0047] The reaction in the prepolymer step may be performed at 50 to 120° C. for 1 to 10 hours, for example.

[0048] The above-mentioned prepolymer step can be carried out by using the following devices: a reactor equipped with a stirring blade; a kneading machine such as a kneader, a continuous kneader, a conical roll, a single-screw extruder, a twin-screw extruder, a triple-screw extruder, a universal mixer, a Plastmill, a body-type (Bodie) mixer, etc.; a rotary dispersion mixer such as a TK homomixer, a Fill Mix, an Ebara Milder, a Claire Mix, an ULTRA-TURRAX, an emulsifying disperser (Cavitron), a biomixer, etc.; an ultrasonic dispersing device; a device such as an in-line mixer that has no moving parts and can mix by the flow of the fluid itself, etc.

[0049] The emulsification step is preferably carried out at a temperature at which water does not evaporate, for example, a temperature in the range of 10 to 90° C. The emulsification step can be carried out using the same equipment as the prepolymer step. Among them, a kneading machine is preferably used, and a twin-screw extruder is more preferably used, from the perspective of being able to easily obtain a urethane resin aqueous dispersion having a high urethane resin content.

[0050] The chain extension step is a step of increasing the molecular weight of the urethane prepolymer (i) by reacting the isocyanate group of the urethane prepolymer (i) with the chain extender (a1) to obtain the urethane resin (X). The temperature during the chain extension step is preferably 50° C. or less from the perspective of productivity.

[0051] The molar ratio of the isocyanate group of the urethane prepolymer (i) to the total of the hydroxyl group and the amino group of the chain extender (a1) [(hydroxyl group and amino group) / isocyanate group] in the chain extension step is preferably in the range of 0.8 to 1.1, more preferably in the range of 0.9 to 1, from the viewpoint of obtaining better film-forming properties and mechanical strength.

[0052] The chain extension step can be performed using the same equipment as in the prepolymer step.

[0053] Next, the foam seat of the present invention will be described.

[0054] The foam sheet can be produced by obtaining a foam liquid from the aqueous dispersion of the urethane resin (X), applying the foam liquid to a substrate, and drying the resulting foam liquid.

[0055] As a method for obtaining a foam liquid from the aqueous dispersion of the urethane resin (X), for example, stirring by hand, using a mixer such as a mechanical mixer, introducing air, an inert gas, etc. can be cited. When using a mixer, for example, a method of stirring at 500 to 3000 rpm for 10 seconds to 3 minutes can be cited. At this time, from the viewpoint of easily adjusting the density of the foamed urethane sheet to a preferred range, the volume before and after foaming is preferably 1.3 to 7 times, more preferably 1.2 to 2 times, and even more preferably 1.3 to 1.7 times.

[0056] Examples of a method for applying the obtained bubble liquid to a substrate such as release paper include a method using a roll coater, a knife coater, a comma coater, an applicator, and the like.

[0057] Examples of a method for drying the coated material include a method of drying at a temperature of 60 to 130° C. for 30 seconds to 10 minutes.

[0058] The thickness of the foamed sheet obtained by the above method is, for example, 5 to 200 μm.

[0059] The density of the foam sheet is preferably 200 to 1000 kg / m2 in order to obtain a more excellent hand feel and peel strength. 3 The range is more preferably 300 to 900 kg / m 3 The range is more preferably 400 to 800 kg / m 3 It should be noted that the density of the foamed urethane sheet refers to a value calculated by dividing the mass of the foamed urethane sheet by the volume.

[0060] Next, the synthetic leather of the present invention will be described.

[0061] The synthetic leather of the present invention comprises at least a substrate (i) and a polyurethane layer (ii), wherein the polyurethane layer (ii) is formed of the foam sheet.

[0062] As a method for producing the above-mentioned synthetic leather, for example:

[0063] (X) a method of obtaining a foam liquid from the above-mentioned urethane resin composition, applying the foam liquid on a release paper, drying it, and laminating it with the above-mentioned substrate (i),

[0064] (Y) a method of obtaining a foaming liquid from the above-mentioned urethane resin composition, applying the foaming liquid to a skin layer formed on a release paper, drying it, and laminating it to the above-mentioned substrate (i),

[0065] (Z) A method of obtaining a foam liquid from the urethane resin composition, applying the foam liquid to the substrate (i), drying the foam liquid, and laminating a skin layer (iii) prepared on a release paper thereon as required.

[0066] As the above-mentioned substrate (i), for example, fiber substrates such as non-woven fabrics, woven fabrics, knitted fabrics based on polyester fibers, polyethylene fibers, nylon fibers, acrylic fibers, polyurethane fibers, acetate fibers, rayon fibers, polylactic acid fibers, cotton, linen, silk, wool, glass fibers, carbon fibers, and blended fibers thereof can be used; substrates obtained by impregnating the above-mentioned non-woven fabrics with resins such as polyurethane resins; substrates obtained by further providing a porous layer on the above-mentioned non-woven fabrics; resin substrates such as thermoplastic urethane (TPU), etc. can be used.

[0067] The polyurethane layer (ii) is formed of the foam sheet, and its density is preferably 200 to 1000 kg / m2 in order to obtain a synthetic leather having both excellent hand feel and peel strength. 3 The range is preferably 300 to 900 kg / m 3 The range is more preferably 400 to 800 kg / m 3 It should be noted that the density of the polyurethane layer (ii) is a value obtained by subtracting the weight of the substrate (i) per 10 cm square from the weight of the synthetic leather per 10 cm square and dividing it by the thickness of the polyurethane layer (ii). It should be noted that the density of the polyurethane layer (ii) can be adjusted according to the foaming condition of the urethane resin composition.

[0068] As the above-mentioned epidermis layer (iii), it is possible to form it by a known method using a known material, for example, a solvent-based urethane resin, a water-based urethane resin, a silicone resin, a polypropylene resin, a polyester resin, etc. can be used. When a soft feel, heat resistance, and hydrolysis resistance are important, a polycarbonate-based urethane resin is preferably used. In addition, in order to reduce DMF when dealing with the environment, a water-based polycarbonate-based urethane resin is more preferably used.

[0069] A surface treatment layer (iv) may be provided on the skin layer (iii) as required for the purpose of improving scratch resistance, etc. The surface treatment layer (iv) may be formed using a known material by a known method.

[0070] [Example]

[0071] Hereinafter, the present invention will be described in more detail using examples.

[0072] [Synthesis example 1]

[0073] In the presence of 0.1 parts by mass of stannous octoate, 1000 parts by mass of a polyether polyol (“PTMG2000” manufactured by Mitsubishi Chemical Corporation, number average molecular weight: 2000, hereinafter referred to as “PTMG2000”), 24 parts by mass of 2,2-dimethylolpropionic acid (hereinafter referred to as “DMPA”), and 262 parts by mass of dicyclohexylmethane diisocyanate (hereinafter referred to as “HMDI”) were reacted at 100° C. until the NCO% reached 2.1% by mass to obtain a urethane prepolymer A1.

[0074] A1 heated to 70°C, triethylamine, a 20 mass % aqueous solution of sodium dodecylbenzenesulfonate ("NEOGEN S-20F" manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) as an emulsifier, and water were simultaneously supplied to a twin-screw extruder (TEM-18SS: manufactured by Toshiba Machine) and mixed to obtain an emulsion. The flow rates of the supplied liquids were 10 kg / hour for A1, 0.2 kg / hour for triethylamine, 2.5 kg / hour for the aqueous emulsifier solution, and 5.1 kg / hour for water, and the operating conditions of the twin-screw extruder were 50°C and 260 rpm.

[0075] Immediately thereafter, a water-diluted solution of isophoronediamine (hereinafter abbreviated as "IPDA") having an amino group content corresponding to 95% of the NCO group was added to extend the chain, thereby finally obtaining a polyurethane emulsion (X-1) having a urethane resin content of 50% by mass.

[0076] [Synthesis example 2]

[0077] In the presence of 0.1 parts by mass of stannous octoate, 1000 parts by mass of PTMG2000, 24 parts by mass of DMPA, and 262 parts by mass of HMDI were reacted at 100° C. until the NCO% reached 2.1% by mass, thereby obtaining a urethane prepolymer A2.

[0078] A2 heated to 70°C, triethylamine, a polypropylene polyethylene copolymer ("Pluronic L-64" manufactured by ADEKA Corporation) as an emulsifier, and water were simultaneously supplied to a twin-screw extruder (TEM-18SS: manufactured by Toshiba Machine) and mixed to obtain an emulsion. The flow rates of the supplied liquids were 10 kg / hour for A2, 0.2 kg / hour for triethylamine, 0.5 kg / hour for L-64, and 7.1 kg / hour for water, and the operating conditions of the twin-screw extruder were 50°C and 260 rpm.

[0079] Then, a water-diluted solution of IPDA having an amino group content corresponding to 95% of the NCO group was immediately added to extend the chain, thereby finally obtaining a polyurethane emulsion (X-2) having a urethane resin content of 50% by mass.

[0080] [Synthesis example 3]

[0081] In the presence of 0.1 parts by mass of stannous octoate, 1000 parts by mass of PTMG2000, 24 parts by mass of DMPA, and 262 parts by mass of HMDI were reacted at 100° C. until the NCO% reached 2.1% by mass to obtain a urethane prepolymer A3.

[0082] A3, triethylamine and water heated to 70°C were simultaneously supplied to a twin-screw extruder (TEM-18SS: manufactured by Toshiba Machinery) and mixed to obtain an emulsion. The flow rates of the supplied liquids were 10 kg / hour for A3, 0.2 kg / hour for triethylamine and 6.6 kg / hour for water, and the twin-screw extruder was operated at 50°C and 260 rpm.

[0083] Then, a water-diluted solution of IPDA having an amino group content corresponding to 95% of the NCO group was immediately added to extend the chain, thereby finally obtaining a polyurethane emulsion (X-3) having a urethane resin content of 50% by mass.

[0084] [Synthesis Example 4]

[0085] In the presence of 0.1 parts by mass of stannous octoate, 1000 parts by mass of PTMG2000, 18 parts by mass of polyethylene glycol ("PEG600" manufactured by NOF Corporation, number average molecular weight: 600, hereinafter abbreviated as "PEG") and 262 parts by mass of HMDI were reacted at 100°C until the NCO% reached 3.1% by mass to obtain a urethane prepolymer A4.

[0086] A4 heated to 70°C, a 20 mass % aqueous solution of sodium dodecylbenzenesulfonate ("NEOGEN S-20F" manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) as an emulsifier, and water were simultaneously supplied to a twin-screw extruder (TEM-18SS: manufactured by Toshiba Machine) and mixed to obtain an emulsion. The flow rates of the supplied liquids were 10 kg / hour for A4, 2.5 kg / hour for the aqueous emulsifier solution, and 0.1 kg / hour for water, and the operating conditions of the twin-screw extruder were 50°C and 260 rpm.

[0087] Then, a water-diluted solution of IPDA having an amino group content corresponding to 95% of the NCO group was immediately added to extend the chain, thereby finally obtaining a polyurethane emulsion (X-4) having a urethane resin content of 60% by mass.

[0088] [Synthesis example 5]

[0089] In the presence of 0.1 parts by mass of stannous octoate, 1000 parts by mass of PTMG2000, 18 parts by mass of PEG, and 262 parts by mass of HMDI were reacted at 100° C. until the NCO% reached 3.1% by mass, thereby obtaining a urethane prepolymer A5.

[0090] A5 heated to 70°C, a polypropylene polyethylene copolymer ("Pluronic L-64" manufactured by ADEKA Corporation) as an emulsifier, and water were simultaneously supplied to a twin-screw extruder (TEM-18SS: manufactured by Toshiba Machine) and mixed to obtain an emulsion. The flow rates of the supplied liquids were 10 kg / hour for A5, 0.5 kg / hour for emulsifier, and 5.8 kg / hour for water, and the operating conditions of the twin-screw extruder were 50°C and 260 rpm.

[0091] Then, a water-diluted solution of IPDA having an amino group content corresponding to 95% of the NCO group was immediately added to extend the chain, thereby finally obtaining a polyurethane emulsion (X-5) having a urethane resin content of 60% by mass.

[0092] [Synthesis example 6]

[0093] In the presence of 0.1 parts by mass of stannous octoate, 1000 parts by mass of PTMG2000, 18 parts by mass of polyethylene glycol dimethyl ether ("M550" manufactured by NOF Corporation, number average molecular weight: 550, hereinafter abbreviated as "MPEG") and 262 parts by mass of HMDI were reacted at 100°C until the NCO% reached 3.3% by mass to obtain a urethane prepolymer A6.

[0094] A6 and water heated to 70°C were simultaneously fed to a twin-screw extruder (TEM-18SS: manufactured by Toshiba Machine) and mixed to obtain an emulsion. The flow rates of the fed liquids were 10 kg / hour for A6 and 4.9 kg / hour for water, and the twin-screw extruder was operated at 50°C and 260 rpm.

[0095] Then, a water-diluted solution of IPDA having an amino group content corresponding to 95% of the NCO group was immediately added to extend the chain, thereby finally obtaining a polyurethane emulsion (X-6) having a urethane resin content of 50% by mass.

[0096] [Synthesis Example 7]

[0097] In the presence of 0.1 parts by mass of stannous octoate, 1000 parts by mass of PTMG2000, 18 parts by mass of PEG, and 262 parts by mass of HMDI were reacted at 100° C. until the NCO% reached 3.1% by mass to obtain a urethane prepolymer A7.

[0098] A7 heated to 70°C, a 20% by mass aqueous solution of sodium dodecylbenzenesulfonate ("NEOGEN S-20F" manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), a polypropylene polyethylene copolymer ("Pluronic L-64" manufactured by ADEKA Co., Ltd.), and water as an emulsifier were simultaneously supplied to a twin-screw extruder (TEM-18SS: manufactured by Toshiba Machine) and mixed to obtain an emulsion. The flow rates of the supplied liquids were 10 kg / hour for A7, 1.3 kg / hour for the aqueous solution of the emulsifier S-20F, 0.3 kg / hour for the emulsifier L-64, and 1.1 kg / hour for water, and the operating conditions of the twin-screw extruder were 50°C and 260 rpm.

[0099] Then, a water-diluted solution of ethylenediamine (hereinafter abbreviated as "EA") having an amino group content corresponding to 95% of the NCO group was immediately added to extend the chain, thereby finally obtaining a polyurethane emulsion (X-7) having a urethane resin content of 60% by mass.

[0100] [Comparative Synthesis Example 1]

[0101] In the presence of 0.1 parts by mass of stannous octoate, 1000 parts by mass of PTMG2000, 34 parts by mass of DMPA, and 262 parts by mass of HMDI were reacted at 100° C. until the NCO% reached 1.6% by mass, thereby obtaining a urethane prepolymer A′1.

[0102] A'1 heated to 70°C, triethylamine, a 20 mass % aqueous solution of sodium dodecylbenzenesulfonate ("NEOGEN S-20F" manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) as an emulsifier, and water were simultaneously supplied to a twin-screw extruder (TEM-18SS: manufactured by Toshiba Machine) and mixed to obtain an emulsion.

[0103] It should be noted that the supply liquid and the operating conditions of the twin-screw extruder were made the same as in Example 1, and an attempt was made to produce a polyurethane emulsion with a solid content concentration of 50%. A water-diluted solution of IPDA having an amino group content equivalent to 95% of the NCO group was immediately added to the obtained emulsion to extend the chain, but gelation occurred and therefore no emulsion could be obtained.

[0104] Therefore, the polyurethane emulsion was produced by increasing the amount of water and reducing the solid content. The flow rates of the supplied liquids were A'1: 10 kg / hour, triethylamine: 0.2 kg / hour, emulsifier aqueous solution: 2.5 kg / hour, water: 19.6 kg / hour, and the twin-screw extruder was operated at 50°C and 260 rpm.

[0105] Then, a water-diluted solution of IPDA having an amino group content corresponding to 95% of the NCO group was immediately added to extend the chain, thereby finally obtaining a polyurethane emulsion (XR-1) having a urethane resin content of 30% by mass.

[0106] [Comparative Synthesis Example 2]

[0107] In the presence of 0.1 parts by mass of stannous octoate, 1000 parts by mass of PTMG2000, 34 parts by mass of DMPA, and 262 parts by mass of HMDI were reacted at 100° C. until the NCO% reached 1.6% by mass, thereby obtaining a urethane prepolymer A′2.

[0108] A'2 heated to 70°C, triethylamine, a polypropylene polyethylene copolymer ("Pluronic L-64" manufactured by ADEKA Corporation) as an emulsifier, and water were simultaneously supplied to a twin-screw extruder (TEM-18SS: manufactured by Toshiba Machine) and mixed to obtain an emulsion.

[0109] It should be noted that the supply liquid and the operating conditions of the twin-screw extruder were the same as in Example 2, and an attempt was made to produce a polyurethane emulsion having a urethane resin content of 50% by mass. A water-diluted solution of IPDA having an amino group content equivalent to 95% of the NCO group was immediately added to the obtained emulsion to extend the chain, but gelation occurred and therefore no emulsion could be obtained.

[0110] Therefore, the polyurethane emulsion was produced by increasing the amount of water and reducing the solid content. The flow rates of the supplied liquids were A'2: 10 kg / hour, triethylamine: 0.2 kg / hour, emulsifier aqueous solution: 0.5 kg / hour, water: 21.6 kg / hour, and the twin-screw extruder was operated at 50°C and 260 rpm.

[0111] Then, a water-diluted solution of IPDA having an amino group content corresponding to 95% of the NCO group was immediately added to extend the chain, thereby finally obtaining a polyurethane emulsion (XR-2) having a urethane resin content of 30% by mass.

[0112] [Comparative Synthesis Example 3]

[0113] In the presence of 0.1 parts by mass of stannous octoate, 1000 parts by mass of PTMG2000, 34 parts by mass of DMPA, and 262 parts by mass of HMDI were reacted at 100° C. until the NCO% reached 1.6% by mass, thereby obtaining a urethane prepolymer A′3.

[0114] A'3, triethylamine, and water heated to 70° C. were simultaneously supplied to a twin-screw extruder (TEM-18SS: manufactured by Toshiba Machine Co., Ltd.) and mixed to obtain an emulsion.

[0115] It should be noted that the supply liquid and the operating conditions of the twin-screw extruder were the same as in Example 3, and an attempt was made to produce a polyurethane emulsion having a urethane resin content of 50% by mass. A water-diluted solution of IPDA having an amino group content equivalent to 95% of the NCO group was immediately added to the obtained emulsion to extend the chain, but gelation occurred and therefore no emulsion could be obtained.

[0116] Therefore, the polyurethane emulsion was produced by increasing the amount of water and reducing the solid content. The flow rates of the supplied liquids A'3 were: 10 kg / hour, triethylamine: 0.2 kg / hour, emulsifier aqueous solution: 0.5 kg / hour, water: 20.4 kg / hour, and the twin-screw extruder was operated at 50°C and 260 rpm.

[0117] Then, a water-diluted solution of IPDA having an amino group content corresponding to 95% of the NCO group was immediately added to extend the chain, thereby finally obtaining a polyurethane emulsion (XR-3) having a urethane resin content of 30% by mass.

[0118] [Comparative Synthesis Example 4]

[0119] In the presence of 0.1 parts by mass of stannous octoate, 1000 parts by mass of PTMG2000, 75 parts by mass of PEG, and 262 parts by mass of HMDI were reacted at 100° C. until the NCO% reached 2.4% by mass, thereby obtaining a urethane prepolymer A′4.

[0120] A'4 heated to 70°C, a 20 mass% aqueous solution of sodium dodecylbenzenesulfonate ("NEOGEN S-20F" manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) as an emulsifier, and water were simultaneously supplied to a twin-screw extruder (TEM-18SS: manufactured by Toshiba Machine) and mixed to obtain an emulsion.

[0121] It should be noted that the supply liquid and the operating conditions of the twin-screw extruder were the same as in Example 4, and an attempt was made to produce a polyurethane emulsion having a urethane resin content of 60% by mass. A water-diluted solution of IPDA having an amino group content equivalent to 95% of the NCO group was immediately added to the obtained emulsion to extend the chain, but gelation occurred and therefore no emulsion could be obtained.

[0122] Therefore, the polyurethane emulsion was produced by increasing the amount of water and reducing the solid content. The flow rates of the supplied liquids were A'4: 10 kg / hour, emulsifier aqueous solution: 2.5 kg / hour, water: 9.3 kg / hour, and the twin-screw extruder was operated at 50°C and 260 rpm.

[0123] Then, a water-diluted solution of IPDA having an amino group content corresponding to 95% of the NCO group was immediately added to extend the chain, thereby finally obtaining a polyurethane emulsion (XR-4) having a urethane resin content of 40% by mass.

[0124] [Comparative Synthesis Example 5]

[0125] In the presence of 0.1 parts by mass of stannous octoate, 1000 parts by mass of PTMG2000, 75 parts by mass of PEG, and 262 parts by mass of HMDI were reacted at 100° C. until the NCO% reached 2.4% by mass to obtain a urethane prepolymer A′5.

[0126] A'5 heated to 70°C, a 20 mass% aqueous solution of sodium dodecylbenzenesulfonate ("NEOGEN S-20F" manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) as an emulsifier, and water were simultaneously supplied to a twin-screw extruder (TEM-18SS: manufactured by Toshiba Machine) and mixed to obtain an emulsion.

[0127] It should be noted that the supply liquid and the operating conditions of the twin-screw extruder were the same as in Example 5, and an attempt was made to produce a polyurethane emulsion having a urethane resin content of 50% by mass. A water-diluted solution of IPDA having an amino group content equivalent to 95% of the NCO group was immediately added to the obtained emulsion to extend the chain, but gelation occurred and therefore no emulsion could be obtained.

[0128] Therefore, the polyurethane emulsion was produced by increasing the amount of water and reducing the solid content. The flow rates of the supplied liquids were A'5: 10 kg / hour, emulsifier aqueous solution: 0.5 kg / hour, water: 11.3 kg / hour, and the twin-screw extruder was operated at 50°C and 260 rpm.

[0129] Then, a water-diluted solution of IPDA having an amino group content corresponding to 95% of the NCO group was immediately added to extend the chain, thereby finally obtaining a polyurethane emulsion (XR-5) having a urethane resin content of 40% by mass.

[0130] [Comparative Synthesis Example 6]

[0131] In the presence of 0.1 parts by mass of stannous octoate, 1000 parts by mass of PTMG2000, 69 parts by mass of MPEG, and 262 parts by mass of HMDI were reacted at 100° C. until the NCO% reached 2.8% by mass, thereby obtaining a urethane prepolymer A′6.

[0132] A'6 and water heated to 70° C. were simultaneously supplied to a twin-screw extruder (TEM-18SS: manufactured by Toshiba Machine) and mixed to obtain an emulsion.

[0133] It should be noted that the supply liquid and the operating conditions of the twin-screw extruder were the same as in Example 6, and an attempt was made to produce a polyurethane emulsion having a urethane resin content of 50% by mass. A water-diluted solution of IPDA having an amino group content equivalent to 95% of the NCO group was immediately added to the obtained emulsion to extend the chain, but gelation occurred and therefore no emulsion could be obtained.

[0134] Therefore, the polyurethane emulsion was produced by increasing the amount of water and reducing the solid content. The flow rates of the supplied liquids were A'6: 10 kg / hour, water: 10.3 kg / hour, and the operating conditions of the twin-screw extruder were 50° C. and 260 rpm.

[0135] Then, a water-diluted solution of IPDA having an amino group content corresponding to 95% of the NCO group was immediately added to extend the chain, thereby finally obtaining a polyurethane emulsion (XR-6) having a urethane resin content of 40% by mass.

[0136] [Example 1]

[0137] 1000 parts by mass of the polyurethane emulsion (X-1) obtained in Synthesis Example 1 and 2 parts by mass of a thickener ("Borchi Gel ALA" manufactured by Borchers) were stirred at 2000 rpm using a mechanical mixer to prepare a mixed liquid. Next, the mixed liquid and air were continuously supplied to a rotor-stator continuous mixer ("MagicLab" manufactured by IKA) to mix and obtain a foam liquid. At this time, the volume and weight of the foam liquid were measured and the density was calculated, and the amount of air supplied was adjusted so that the density of the foam liquid became 2 / 3.

[0138] [Evaluation method of foam retention]

[0139] (1) Appearance evaluation

[0140] The obtained foam liquid was applied to a polyester woven fabric using a bar coater to a thickness of 1000 μm, and dried at 70° C. for 2 minutes and further at 120° C. for 2 minutes using a hot air dryer to form a processed fabric, and the foam retention was evaluated as follows.

[0141] "A": The polyurethane layer formed a foamed sheet having good appearance.

[0142] "B": Cracks occurred in the polyurethane layer.

[0143] "C": Bubbles disappeared from the polyurethane layer.

[0144] (2) Microscopic evaluation

[0145] The cross section of the obtained processed cloth was observed using a scanning electron microscope ("SU3500" manufactured by Hitachi High-Tech Co., Ltd., magnification 200 times) and evaluated as follows.

[0146] "T": Bubbles were confirmed in the polyurethane layer.

[0147] "F": No bubbles were confirmed in the polyurethane layer.

[0148] [Evaluation method of hand feel]

[0149] The obtained processed fabric was evaluated by touch as follows.

[0150] "A": Rich in softness.

[0151] "B": Slightly soft.

[0152] "C": Poor softness.

[0153] "D": Hard.

[0154] [Evaluation method of peel strength]

[0155] A 2.5 cm wide hot melt tape ("BW-2" manufactured by SAN CHEMICALS Co., Ltd.) was placed on the surface of the polyurethane layer of the processed fabric obtained, and heated at 150°C for 30 seconds for bonding. The sample was cut along the width of the hot melt tape. A portion of the sample was peeled off, and the substrate and the hot melt tape were clamped with a chuck, and the peel strength was measured using an Autograph (manufactured by Shimadzu Corporation). The average value of the obtained data was calculated, converted to a width of 1 cm, and evaluated as follows.

[0156] "T": The peel strength is 3.0 (kgf / cm) or more.

[0157] "F": Peel strength is less than 3.0 (kgf / cm).

[0158] [Evaluation method of foam sheet density]

[0159] The processed fabric was cut into 10 cm squares and weighed. The thickness was also measured using a thickness gauge. The density of the foam sheet was calculated according to the following formula (1) based on the difference between the weight and thickness of the polyester woven fabric weighed and measured in the same manner.

[0160]

[0161] [Method for measuring number average molecular weight, etc.]

[0162] The number average molecular weight of the polyols and the like used in the Synthesis Examples and Comparative Synthesis Examples refers to the value measured by gel permeation column chromatography (GPC) under the following conditions.

[0163] Measuring device: High-speed GPC device ("HLC-8220GPC" manufactured by Tosoh Corporation)

[0164] Column: The following columns manufactured by Tosoh Corporation were connected in series and used.

[0165] "TSKgel G5000" (7.8mm I.D. × 30cm) × 1 piece

[0166] "TSKgel G4000" (7.8mm I.D. × 30cm) × 1 piece

[0167] "TSKgel G3000" (7.8mm I.D. × 30cm) × 1 piece

[0168] "TSKgel G2000" (7.8mm I.D. × 30cm) × 1 piece

[0169] Detector: RI (differential refractometer)

[0170] Column temperature: 40°C

[0171] Eluent: Tetrahydrofuran (THF)

[0172] Flow rate: 1.0mL / min

[0173] Injection volume: 100 μL (tetrahydrofuran solution with a sample concentration of 0.4 mass%)

[0174] Standard sample: The standard curve was prepared using the following standard polystyrene.

[0175] (Standard Polystyrene)

[0176] "TSKgel Standard Polystyrene A-500" manufactured by Tosoh Corporation

[0177] "TSKgel Standard Polystyrene A-1000" manufactured by Tosoh Corporation

[0178] "TSKgel Standard Polystyrene A-2500" manufactured by Tosoh Corporation

[0179] "TSKgel Standard Polystyrene A-5000" manufactured by Tosoh Corporation

[0180] "TSKgel Standard Polystyrene F-1" manufactured by Tosoh Corporation

[0181] "TSKgel Standard Polystyrene F-2" manufactured by Tosoh Corporation

[0182] "TSKgel Standard Polystyrene F-4" manufactured by Tosoh Corporation

[0183] "TSKgel Standard Polystyrene F-10" manufactured by Tosoh Corporation

[0184] "TSKgel Standard Polystyrene F-20" manufactured by Tosoh Corporation

[0185] "TSKgel Standard Polystyrene F-40" manufactured by Tosoh Corporation

[0186] "TSKgel Standard Polystyrene F-80" manufactured by Tosoh Corporation

[0187] "TSKgel Standard Polystyrene F-128" manufactured by Tosoh Corporation

[0188] "TSKgel Standard Polystyrene F-288" manufactured by Tosoh Corporation

[0189] "TSKgel Standard Polystyrene F-550" manufactured by Tosoh Corporation

[0190] [Method for measuring average particle size of urethane resin (X)]

[0191] The urethane resin aqueous dispersions obtained in Examples and Comparative Examples were measured for average particle size using a laser diffraction / scattering particle size distribution analyzer ("LA-910" manufactured by Horiba, Ltd.) with water as the dispersion liquid at a relative refractive index of 1.10 and a particle size basis of area.

[0192] [Examples 2 to 7, Comparative Examples 1 to 6]

[0193] Except having changed the type of the polyurethane emulsion (X-1) used as shown in Tables 1 to 2, the same operation as in Example 1 was carried out to obtain processed cloth, and the foam retention, hand feeling and peel strength were evaluated.

[0194]

Table 1

[0195]

[0196]

Table 2

[0197]

[0198] It is understood that the foamed sheet of the present invention can stably obtain a water dispersion of a urethane resin as shown in Examples 1 to 7, and has excellent film-forming properties.

[0199] On the other hand, Comparative Examples 1 to 3 are embodiments in which a urethane resin having an anionic group whose content of the urethane resin (X) is lower than the range specified in the present invention is used, but the foam retention and hand feel are poor. Comparative Examples 4 to 6 are embodiments in which a urethane resin having a nonionic group whose content of the urethane resin (X) is lower than the range specified in the present invention is used, but the peel strength is poor.

Claims

1. A foam sheet, characterized in that: A foamed sheet formed from a water dispersion of a urethane resin (X). The urethane resin (X) has a nonionic group. The urethane resin (X) is made of a polyether polyol having an oxyethylene structure and a polyol (a2) other than the polyether polyol having an oxyethylene structure, wherein the proportion of the polyether polyol having an oxyethylene structure in the total mass of the raw materials constituting the urethane resin (X) is 0.25% by mass to 5% by mass. The content of the urethane resin (X) in the aqueous dispersion is 50% by mass to 80% by mass, and the aqueous dispersion does not contain an organic solvent in its production process.

2. The foam sheet according to claim 1, having a density of 200 kg / m 3 ~1000kg / m 3 .

3. The foam sheet according to claim 1 or 2, wherein The urethane resin (X) uses a chain extender (a1) as a raw material.

4. The foam sheet according to claim 3, wherein The chain extender (a1) has an amino group.

5. The foam sheet according to any one of claims 1 to 4, wherein The average particle size of the urethane resin (X) is in the range of 0.01 μm to 1 μm.

6. A synthetic leather, characterized in that: At least comprising a substrate (i) and a polyurethane layer (ii), The polyurethane layer (ii) is formed of the foam sheet according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Heat-expandable sewing thread and sewing method using the same

    JP2013119688A

  • Method for preparing carboxylic acid / sulfonic acid mixed waterborne polyurethane with high solid content with solvent-free process

    CN107522841A

  • Method for producing fiber laminate, fiber laminate and synthetic leather

    JP2005273083A